MENTAL HEALTH DYNAMICS IN THE CONTEXT OF COLLECTIVIST CULTURE: A STUDY OF INDIGENOUS COMMUNITIES IN INDONESIA - Virdiyanti, Ruri (Lafadz Jaya Publisher, 2025)
The dynamics of mental health are significantly shaped by cultural factors, and collectivist cultures offer a unique lens for understanding mental well-being. This study explores mental health within the context of collectivist culture in Indonesia, focusing specifically on indigenous communities. Indonesia, with its vast array of indigenous cultures, presents a unique environment to examine how traditional practices, communal values, and social cohesion affect mental health outcomes. This paper explores how the interplay of cultural norms, community relationships, and traditional coping mechanisms influences individual and collective mental health. Utilizing a qualitative approach, the study employs interviews, focus groups, and ethnographic observation in indigenous communities across Java, Bali, and Sumatra. The results suggest that the collectivist orientation, which emphasizes social harmony, interdependence, and familial ties, has both positive and negative effects on mental health. On the one hand, community support and collective responsibility foster resilience and reduce the stigma associated with mental health issues. On the other hand, the pressure to conform to societal norms and uphold collective values can lead to feelings of isolation, stress, and suppression of individual mental health needs. The findings contribute to a deeper understanding of mental health in collectivist societies and provide valuable insights into culturally sensitive mental health interventions. The paper concludes with implications for mental health policy and practices in indigenous communities and the broader Southeast Asian region.